Precision Flux Control of Linear Reluctance Actuator Using the Integral Sliding Mode Method - Miao, Qian; Liu, Yang; Tan, Jiu Bin (Frontiers in Energy Research, 2022)
The performance of actuator is becoming increasingly important in ultra-precision stage. However, the traditional Lorentz motors with given mechanical parameters can not provide enough force for the next-generation motion stage in the semiconductor industry since it achieve physical limit of power factor. To tackle this problem, this paper develops a novel driven approach and its control strategy for high-dynamic stages. Explicitly, the proposed method utilizes linear reluctance motor as actuator, which could promote the continuous thrust significantly. A heuristic optimization based Bouc-wen model is established to describe the nonlinear behavior of the novel actuator. And a flux control algorithm based on integral sliding mode is derived and adjusted for precision thrust generation. Comparative simulations on a specific linear reluctance motor confirm the effectiveness and superiority of the proposed method, and show that it has the ability to conquer the force nonlinearity of the novel actuator.